Cortical recruitment and functional dynamics in postural control adaptation and habituation during vibratory proprioceptive stimulation. (13th March 2019) - Edmunds, K J; Petersen, H; Hassan, M; Yassine, S; Olivieri, A; Barollo, F; Friðriksdóttir, R; Edmunds, P; Gíslason, M K; Fratini, A; Gargiulo, P
Abstract: Objective . Maintaining upright posture is a complex task governed by the integration of afferent sensorimotor and visual information with compensatory neuromuscular reactions. The objective of the present work was to characterize the visual dependency and functional dynamics of cortical activation during postural control. Approach . Proprioceptic vibratory stimulation of calf muscles at 85 Hz was performed to evoke postural perturbation in open-eye (OE) and closed-eye (CE) experimental trials, with pseudorandom binary stimulation phases divided into four segments of 16 stimuli. 64-channel EEG was recorded at 512 Hz, with perturbation epochs defined using bipolar electrodes placed proximal to each vibrator. Power spectra variation and linearity analysis was performed via fast Fourier transformation into six frequency bands (Δ, 0.5–3.5 Hz; θ, 3.5–7.5 Hz; α, 7.5–12.5 Hz; β, 12.5–30 Hz;, 30–50 Hz; and, 50–80 Hz). Finally, functional connectivity assessment was explored via network segregation and integration analyses. Main results . Spectra variation showed waveform and vision-dependent activation within cortical regions specific to both postural adaptation and habituation. Generalized spectral variation yielded significant shifts from low to high frequencies in CE adaptation trials, with overall activity suppressed in habituation; OE trials showed the opposite phenomenon, with both adaptation and habituation yielding increases in spectral power. Finally, our analysis of functional dynamics reveals novel cortical networks implicated in postural control using EEG source-space brain networks. In particular, our reported significant increase in local θ connectivity may signify the planning of corrective steps and/or the analysis of falling consequences, while α band network integration results reflect an inhibition of error detection within the cingulate cortex, likely due to habituation. Significance . Our findings principally suggest that specific cortical waveforms are dependent upon the availability of visual feedback, and we furthermore present the first evidence that local and global brain networks undergo characteristic modification during postural control.